Peningkatan Kompetensi Guru melalui Pelatihan Strategi Pengerjaan TOEFL: Studi Kasus di SMA Muhammadiyah 13 Tomang - Syaadiah Arifin; Hamzah Puadi Ilyas; Risna Saswati (Yayasan Literasi Sains Indonesia, 2025)
The Test of English as a Foreign Language (TOEFL) serves as a key competency assessment, yet many teachers struggle with its format and effective answering strategies. This issue is particularly prominent at SMA Muhammadiyah 13 Tomang, where a significant number of teachers face challenges in preparing students for this exam due to limited exposure to effective test strategies. This study aims to improve teachers' competence through interactive TOEFL strategy training. A mixed-method approach was employed, integrating quantitative and qualitative analysis. Pre-test and post-test measured score improvements, while interviews, observations, and open-ended questionnaires explored participants’ challenges and strategy effectiveness. The three-day training covered Reading, Listening, and Structure sessions, applying skimming, scanning, note-taking, and sentence structure analysis strategies. Results showed improved comprehension in Reading (+19%), Listening (+14%), and Structure (+10%). A paired t-test confirmed a significant increase (p < 0.05). Qualitative findings highlighted that skimming and note-taking were more effective than traditional methods, although grammar comprehension remained a challenge. Beyond improving TOEFL scores, this training enhances English teaching methodologies in schools. Teachers are expected to implement the acquired strategies in classrooms and support students' TOEFL preparation. This study confirms that the mixed-method approach provides a comprehensive understanding of learning strategy effectiveness in enhancing educators’ English proficiency.